Efficient methods for the extraction and microencapsulation of red pigments from a hybrid rose - Ge, Cynthia; Wan, Z.; Song, N.; Fan, A.; Wu, R. (Elsevier, 2009)
Natural pigments have been used preferentially in food and cosmetic production. Recent interest in Yunnanon the potential use of the rose red pigment(s) (RRP) of Rosa hybridum (hybrid tea) cv. Crimson Glory(parentage: Catherine Kordes W.E. Chaplin) which flourishes in plantations as the ‘Yunnan HighlandRose’ (YHR), prompted this study into the development of efficient methods for the extraction and encapsulationof the pigments for wider commercial application. Based on production cost and potential practicalapplication, the best extraction (81.6%) was achieved employing an optimal microwave extractionprocess. Separation under AB-8 macro porous resin has resulted in a 4.5 fold increase in colour valueunits. Microencapsulation in the bee’s-wax: Stearic acid (1:1) mix provided the stability of the pigmentsunder different pH, light and heat and further confirmed that the stability of the product was significantlyenhanced. This is the first report of effective microencapsulation of RRP from the YHR, facilitating commercialapplications for these pigments